Beyond Incentives: Do Schools Use Accountability Rewards Productively? - Bacolod, Marigee; DiNardo, John; Jacobson, Mireille (Journal of business & economic statistics, 2012)
We use a regression discontinuity design to analyze an understudied aspect of school accountability systems-how schools use financial rewards. For two years, California's accountability system financially rewarded schools based on a deterministic function of test scores. Qualifying schools received per-pupil awards amounting to about 1% of statewide per-pupil spending. Corroborating anecdotal evidence that awards were paid out as teacher bonuses, we find no evidence that winning schools purchased more instructional material, increased teacher hiring, or changed the subject-specific composition of their teaching staff. Most importantly, we find no evidence that student achievement increased in winning schools. Supplemental materials for this article are available online.